2022
DOI: 10.21037/atm-22-566
|View full text |Cite
|
Sign up to set email alerts
|

Panax notoginseng attenuates hypoxia-induced glycolysis in colonic mucosal epithelial cells in DSS-induced colitis

Abstract: Background: Colonic mucosal injuries are an important manifestation of ulcerative colitis (UC), which is related to hypoxia-induced glycolysis in colonic mucosal epithelial cells (cmECs). Panax notoginseng (PN) promotes the repair of colonic mucosal injuries by inhibiting hypoxia-induced glycolysis in cmECs; However, the mechanism by which this occurs is not completely clear. Here, we are to investigate the effects of PN on glucose metabolism in cmECs in colitis and the underlying mechanism.Methods: A model of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In a rat model of colitis induced by sodium dextran sulfate, the use of Panax notoginseng ethanol extract promotes the repair of colonic mucosa and microvascular damage in rats with colitis, reduces the inflammatory response, and lowers the disease activity scores [ 20 ]. In addition, in a colitis rat model, Panax notoginseng extract upregulates the expression of ATP4a in mitochondria in colonic mucosal epithelial cells to improve glycolysis, which is strongly associated with the activation of mitochondrial aerobic oxidation [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a rat model of colitis induced by sodium dextran sulfate, the use of Panax notoginseng ethanol extract promotes the repair of colonic mucosa and microvascular damage in rats with colitis, reduces the inflammatory response, and lowers the disease activity scores [ 20 ]. In addition, in a colitis rat model, Panax notoginseng extract upregulates the expression of ATP4a in mitochondria in colonic mucosal epithelial cells to improve glycolysis, which is strongly associated with the activation of mitochondrial aerobic oxidation [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies have reported that components derived from P. notoginseng have many healthcare functions, including cardiovascular protection, neuroprotection, and anticancer and antidiabetic effects (Xu et al., 2019). Furthermore, it is also reported to prevent colonic mucosal injury and inflammation resulting from UC through pyruvate dehydrogenase kinase 4 and gut microbiota (He, Pan, et al., 2022; Wang et al., 2023). The most abundant active ingredients in P. notoginseng are P. notoginseng saponins (PNS), the dammarane‐type saponins, including protopanaxadiol‐type and protopanaxatriol‐type (Liu et al., 2020).…”
Section: Introductionmentioning
confidence: 99%